Type 2 Diabetes Mellitus: Link between Diet, HbA1c and Complications - Sami, Waqas; Ansari, Tahir; Butt, Nadeem Shafique; M. R., Ab Hamid (Australasian Medical Journal, 2016)
Diabetes mellitus is now globally considered as a leading cause of morbidity and mortality. It is associated with high rates of microvascular and macrovascular complications. Regular consumption of high caloric food, poor dietary habits and adoption of sedentary life style has been linked with the development of type 2 diabetes mellitus. The purpose of this review is; to highlight the influence of diet on HbA1c in type 2 diabetics, to explore association between HbA1c and diabetes complications and to propose a dietary consultation model for more effective diabetes care. The literature was reviewed intensively from January – March 2016 through PubMed central, Medscape, Google Scholar and other databases. The keywords and MeSH terms used in this search were “diabetes mellitus”, “glycated haemoglobin”, “type 2 diabetes mellitus”, “diet and type 2 diabetes mellitus” and “diabetes complications”. Dietary management is a superior option for glycaemic control in type 2 diabetes mellitus. It is important to keep the HbA1c level in acceptable range to delay the onset and progression of diabetes complications. In this review, various food groups that can have beneficial and adverse effects on HbA1c have been identified. Moreover, Diabetic Retinopathy (DR) stood out as the most prevalent complication of poorly managed diabetes mellitus in Saudi Arabia. The dimensions of the proposed dietary consultation model are based on the assessment of diabetics’ diabetes mellitus knowledge, dietary knowledge, dietary attitude and dietary practices. This assessment if carried out at the initial stage of Diabetes mellitus can be helpful in delaying the early onset and progression of microvascular and macrovascular diabetes complications.